Vida e evolução no pensamento de Henri Bergson - Rio, Sinomar Ferreira Do [UNIFESP] (2019)
The evolution of life, according to the philosophical perspective of Henri Bergson, develops as a process of creating itself and its conditions of survival. In this reading, evolution shows itself as a élan vital coming from the tension that the tendencies of living in the interior of reality imply, because they tend to update. This vital activity, tensioned with itself, leads to the formation of specific beings and generates, in this totality, own modes of existence that define themselves as self-interests, reflecting a tendency to liberate the natural determinations of a reality solved in itself. From this evolutionary movement, we see, through this philosophy, that only in the human species this individualization and these interests really constitute as specific singularities within the determinations of species and, also in the human species, life seems to take place in a greater degree of freedom. The work develops as a search for understanding of this movement of freedom that life tends to put into effect as its will, putting in discussion the degree of achievement of freedom that life has reached with this species. The discussion of this fundamental question of our work occurs through the appreciation of the impasses that life finds in its evolutionary process when it is involved with materiality in its process of organization. We sought to verify whether life, even in the human species, was detained by the material tendency, restricting itself to conservation movements and, therefore, to self-repetition. This search places us before the thesis that life occurs as a tendency to always advance on the determinations that involve it in its evolutionary trajectory, which leads us to think of the human species as a movement of freedom still to be effective in its own meaning, that is: as the predominantly interior movement of life in creation.